Vineyard area estimation using medium spatial resolution satellite imagery - Rodriguez Perez, J.R.=700 1 Alvarez Lopez, C.J.; Miranda, D.; Alvarez, M.F.
(Es, En)
Ilus., 29 ref.
Keywords: VID; VITIS VINIFERA; TELEDETECCION; AREA DE SUPERFICIE; INVENTARIOS; REGISTRO; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH